Survey of ICT and Education in Africa : Togo Country Report - Agyeman-Duahl, Osei (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Although Togo has no ICT policy in place, a revision to the education policy in 2003 makes reference to the need provide ICT orientation and training for students. However, the lack of resources is constraining government efforts to take significant action. Non-governmental Organizations (NGOs) are active in terms of obtaining computers for a few schools and some private school sare able to maintain computer labs by charging extra fees - a practice that is not affordable for most students in the public system. The Agence Universitaire de La Francophonie (AUF) actively working with several higher education institutions to provide access to computer facilities with high speed Internet connectivity. Television has also been used to train teachers in pedagogy.